Utilizing immunostimulants and probiotics for enhancing vannamei shrimp (Litopenaeus vannamei) aquaculture activities - Syifania Hanifah Samara; Gunanti Mahasri; Rahayu Kusdarwati; Dheani Nur Ahadya Syifa Chaerunissa; Anggun Khoirun Nikmah; Elisabeth Benita Indarmastuti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Vannamei shrimp is one of the important fisheries commodities in Indonesia. This is because vannamei shrimp are expensive, popularly consumed by people around the world, and can be cultured. However, vannamei aquaculture activities are still hampered by disease, less production, and lack of technology implementation. Kedung Pandan Village (Jabon, Sidoarjo, East Java) is one of the potential areas for v vannamei shrimp aquaculture which is also constrained by this issues, so many farmers have gone out of business. This community service activity aims to increase the productivity of vannamei shrimp cultivation by administering immunostimulants and probiotics. In its implementation, this community service activity collaborates with "Putri Mandiri", a group of vaname shrimp farmers in Kedung Pandan Village. This activity is carried out in the stages of preparation, implementation of activities (socialization-demonstration), and evaluation.  Socialization and demonstration activities were carried out on August 9 2023 and were enthusiastically participated by residents. The results of this activity indicate that the knowledge of farmers in Kedung Pandan Village, Jabon, Sidoarjo has increased and can use immunostimulants and probiotics in vannamei shrimp farming activities.